A new fluorescent hemicryptophane for acetylcholine recognition with an unusual recognition mode. (1st July 2020) - Fantozzi, Nicolas; Pétuya, Rémi; Insuasty, Alberto; Long, Augustin; Lefevre, Sara; Schmitt, Aline; Robert, Vincent; Dutasta, Jean-Pierre; Baraille, Isabelle; Guy, Laure; Genin, Emilie; Bégué, Didier; et al.
Abstract : The ammonium of the target interacts with the south part of the hemicryptophane probably because the cyclotriveratrylene's electronic density is altered by the extension of conjugation. Abstract : A new off–on fluorescent hemicryptophane probe for acetylcholine has been designed. This hemicryptophane, made fluorescent via an extension of the conjugation of its cyclotriveratrylene C 3 -symmetry part, exhibits improved fluorescence properties compared with fluorescent hemicryptophanes previously described. Indeed, both the excitation and emission wavelengths are red-shifted and the quantum yield is increased. Moreover, this hemicryptophane is able to bind acetylcholine with a high association constant of 3.2 × 10 4 M −1 . This recognition process is accompanied by an increase in the brightness of the capsule. Surprisingly, contrary to what is commonly observed with cyclotriveratrylene-based hosts, the quaternary ammonium of the guest interacts with the tris(2-aminoethyl)amine south part of the hemicryptophane instead of the cyclotriveratrylene north part. This unusual binding mode is supported by both proton NMR experiments and density functional theory calculations.